Promotional enhancement theory: a model for designing promotions that enhance brand evaluations - Tietje, Brian C (My University, 1999)
It is commonly argued that although sales promotions effectively influence initial brand choice, they may ultimately undermine brand evaluations and repurchase intentions. Prior experimental results demonstrate that under certain conditions, persons who receive a reward for selecting a product exhibit less favorable product evaluations than persons who are offered no reward. These findings conflict with the common wisdom of marketers who use promotions extensively. Either marketers are unconcerned with long-run effects or sales promotions may not have the detrimental effects on brand evaluations predicted by past research.The current research program focuses on positive promotional effects whereby product evaluations are enhanced by rewards. I apply availability valence theory (Tybout, Sternthal and Calder 1983; Hannah and Sternthal 1984) to a reward context and delineate the psychological processes that lead to enhancement effects. I also synthesize empirical evidence from prior research that is consistent with the availability valence explanation. I then construct a theoretical framework termed Promotional Enhancement Theory that links the theoretical concepts from availability valence theory with promotional execution tactics to explain and predict how promotional factors can enhance consumer product evaluations.Initial testing of Promotional Enhancement Theory focuses on how the timing and source of promotions impact product evaluations. A reward timing effect was obtained in Study 1 whereby persons who received an immediate, pre-evaluation reward for choosing a new product reported higher product evaluations than persons who received either no reward or a promised-but-delayed reward that was distributed after product evaluations. Furthermore, the delayed reward undermined evaluations relative to the no-reward condition, presumably due to the enhanced task-contingency of the delayed reward. Study 2 demonstrated that immediate rewards do not enhance product evaluations when the source of the reward is unrelated to the product, suggesting that promotions elicit a favorable evaluation of a product only when the information they provide is considered product relevant. These results suggest that promotions can enhance product evaluations when they elicit consumer perceptions of marketer goodwill and minimize the salience of a promotion's task-contingency by maximizing consumer behavioral freedom.
Thesis (Ph. D.)--University of Washington, 1999
Keywords: Theses--Business administration